Influence of Bacteria on the Permeation Characteristics of Concrete made with Supplementary Cementing Materials - Chahal, Navneet (My University, 2013)
The concrete structures deteriorate in contact with the surroundings which lead to an irreversible damage and ultimately reducing the strength of the structure. The characteristics of pore structure of concrete have a direct influence on its durability. The durability and strength of concrete can be enhanced by using a novel technique which involves bacterial-induced calcite precipitation. Bacteria are capable of precipitating calcium carbonate by providing heterogeneous crystal nucleation sites in super-saturated CaCO3 solution. The initial objective of the research work involved the isolation of urease producing bacteria from alkaline, rhizospheric soil and sewerage sludge. The bacteria were identified by the ability to sustain itself in alkaline environment of cement/concrete. All the bacterial isolates were analysed through DNA sequencing and the bacteria identified as Sporosarcina pasteurii, showed maximum urease production when it was grown on urease agar and broth. The sufficient urease activity allowed application of Sporosarcina pasteurii for biocementation. The significant objective of the research work further involved the use of ureolytic bacteria (Sporosarcina pasteurii) in concrete which would make it, self-healing. The bacteria present in the concrete rapidly sealed freshly formed cracks through calcite production. The bacterial concentrations were optimized to 103,105 and 107 cells/ml. In concrete mix, cement was replaced with fly ash, and silica fume. The percentage replacement of fly ash and silica fume was by weight of cement. The percentage use of fly ash was 0, 10, 20 & 30%, and that of silica fume was 0, 5 & 10%. The experiments were carried out to evaluate the effect of Sporosarcina pasteurii on the compressive strength, water absorption, water porosity and rapid chloride permeability of concrete made with fly ash and silica fume up to the age of 91 days. The test results indicated that inclusion of Sporosarcina pasteurii enhanced the compressive strength, reduced the porosity and permeability of the concrete with fly ash and silica fume. The improvement in compressive strength was due to deposition on the bacteria cell surfaces within the pores which was scanned by electron microscopy and confirmed by XRD which revealed calcium carbonate precipitation. This precipitation reduced the chloride permeability in concrete with fly ash and silica fume. The bacteria improve the impermeability of concrete by improving its pore structure and thereby enhancing the life of concrete structures.
phd, dbtes
Keywords: bacteria; compresive strength